Development of Educational Game Media Based on Problem Based Learning in German Language in the First Grade Senior High School Students SMA Negeri 1 Sibolga - Syahraini Marbun (BIRCU, 2021)
This study aims to: (1) determine the feasibility of problem-based learning educational game media in German language learning (2) to determine the effectiveness of using problem-based learning-based educational game media on German language material. This type of research is development research using the ASSURE product development model and combined with the Dick and Carey learning design model. This research was conducted on class X students at senior high school SMA Negeri 1 Sibolga. The method used in this research is a quasi-experimental method. The research sample consisted of 60 students consisting of 30 students as an experimental class who were taught using educational game media based on problem based learning and 30 students as a control class who were taught using youtube-based learning media. The results of hypothesis testing prove that there is a significant difference between the learning outcomes of students who are taught about self-introduction in German using problem-based educational game learning media and students who are taught using YouTube-based learning media. This is shown by the data acquisition, namely tcount = 11.27 while ttable = 1.695, at a significant level of 0.05 through interpolation ttable 1.695. It is concluded that the effectiveness of German language learning using problem-based educational game learning media is higher than using Youtube-based learning media.